Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1113/jphysiol.2005.082974
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow in guinea fowl Numida meleagris as an indicator of energy expenditure by individual muscles during walking and running

Abstract: Running and walking are mechanically complex activities. Leg muscles must exert forces to support weight and provide stability, do work to accelerate the limbs and body centre of mass, and absorb work to act as brakes. Current understanding of energy use during legged locomotion has been limited by the lack of measurements of energy use by individual muscles. Our study is based on the correlation between blood flow and aerobic energy expenditure in active skeletal muscle during locomotion. This correlation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
80
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 73 publications
9
80
0
Order By: Relevance
“…The ILPO is a biarticular muscle with extensor actions at the hip and the knee (Fig.1). The changes of energy use with speed during level locomotion in guinea fowl, indicate that the ILPO is most important in running, because energy use by this muscle is very low during walking (Ellerby et al, 2005). Evidence from comparative anatomy also suggests that the evolution (or retention) of a large ILPO is specifically associated with fast running in ground dwelling birds.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…The ILPO is a biarticular muscle with extensor actions at the hip and the knee (Fig.1). The changes of energy use with speed during level locomotion in guinea fowl, indicate that the ILPO is most important in running, because energy use by this muscle is very low during walking (Ellerby et al, 2005). Evidence from comparative anatomy also suggests that the evolution (or retention) of a large ILPO is specifically associated with fast running in ground dwelling birds.…”
Section: Introductionmentioning
confidence: 86%
“…Estimates of energy use by the ILPO are based on the rate of blood flow to the muscle during activity (Ellerby et al, 2005;Ellerby and Marsh, 2006;Rubenson et al, 2006). Marsh and Ellerby reviewed the use of muscle blood flow as an indicator of muscle energy use and concluded that for aerobically supported exercise the data from human and animal studies support a linear and proportional relationship between blood flow and energy use .…”
Section: Matching Blood Flow Data From the Literature To Emg Datamentioning
confidence: 99%
See 3 more Smart Citations